Gadolinium deposition in tissue following multiple contrast-enhanced MRI examinations - Mahzary, Othman Mohammed (Journal of medical and pharmaceutical sciences, 2019)
Gadolinium-based contrast agents (GBCAs) were considered extremely safe since their introduction for clinically used in 1988. However, in 2006, nephrogenic systemic fibrosis (NSF) was reported in patients with end-stage renal failure who were exposed to some GBCAs. In 2014, gadolinium deposition was found to occur in the brain tissues of patients exposed to multiple GBCA studies. This project aimed to review currently published studies regarding gadolinium accumulation in tissues after repeated GBCA administrations to identify and summarize the recent findings for this issue. Six scientific databases were electronically searched for relevant studies between 2009 and July 2016. The reference lists were also checked and tracked to find related articles. Studies were evaluated for relevance either by scanning their title and abstracts or reading the full text. The primary search yielded 1765 papers, which were then narrowed down to 14 studies that fulfilled the inclusion criteria. Two more studies were found by manually searching the reference lists. Of these, three studies assessed gadolinium retention in the brain tissues on animal models, while the remaining 13 were human research studies.